Microarray expression profile of genes in rats subjected to spinal cord ischemia. Issue 2 (28th September 2016) - Dan, Qi‐Qin; Hu, Yue; Jin, Hua
Abstract : Objective: Spinal cord ischemia is a common disease with a high mortality and morbidity. It will induce the motor and sensory deficits, which bring heavy burden to the patient, family and society. However, the underlying molecular mechanism remains to be elucidated and the treatment is far from satisfaction. How to search the key moleculares from multiple genes, after spinal cord ischemia may provide the basic orientation for gene therapy in future clinic trial. Methods: Here, sixteen male rats were employed and randomly divided into the sham and spinal cord ischemia group. Aorta blocking was performed to establish the spinal cord ischmic model. Microarray technique was applied to select the differentially expressed genes between the spinal cord ischemia and sham group in spinal cord tissues at 72 h post operation. Gene ontology analysis, including biological process, cellular component and molecular function, and Kyoto Encyclopedia of Genes and Genomes (KEGG). Genomes were adopted to analyze the function and pathway of the differentially expressed genes following spinal cord ischemia. Results: Spinal cord ischemic model was successfully established indicated by disappearing of the caudal pulse. Microassay analysis showed that there were 3984 up‐regulated genes and 3513 down‐regulated genes in spinal cord after ischemia. Of these, neurodegeneration, oxidativve, inflamation have been involved, and various functions and pathways, such as signal pathway of ribosome and oxidative phosphorylation pathway have been involved in these differentially expressed genes. Conclusion: Our results revealed a network of multiple genes involving in neurodegeneration, oxidative, and inflammation exerts main influnce in the spinal cord after ischemia. These findings will provide potentially novel understanding for the treatment of spinal cord ischemia.